RESPON PERTUMBUHAN PADI GOGO (Oryza sativa) KULTIVAR LOKAL PADA BERBAGAI TINGKAT KELENGASAN TANAH - Suete, Ferdian; Samudin, Sakka; Hasanah, Uswah (AGROTEKBIS, 2017)
The purpose of this study was to evaluate the response of the growth of the rice plant (Oryza sativa) local cultivars at different levels of soil moisture. This study uses a randomized complete block design consisting of (1) Cultivars Rice locally as the first factor consisting of (K1) = rice cultivars Ranta, (K2) = rice cultivars njengi and (K3) = rice cultivars Sampara, (2) the level of moisture soil as a second factor consisting of (T1) = The level of moisture the ground 100% (field capacity),              (T2) = level of moisture the soil 75%, (T3) = Level moisture soil 50% and (T4) = rate of moisture land 25% , The results showed that the cultivars njengi generating plant height and stem diameter is greater than the other cultivars. Ranta cultivars showed the number of leaves, number of tillers and leaf area were higher than the other cultivars. Soil moisture level of 100% (field capacity) also results in plant height, number of leaves, number of tillers, leaf greenness (chlorophyll) and a trunk diameter greater than with other soil moisture levels. Key Words : local cultivars, rice, soil moisture.